EFEKTIVITAS FESTIVAL PERAHU BIDAR TRADISIONAL DALAM PENGEMBANGAN WISATA SUNGAI MUSI DI KOTA PALEMBANG - riza adelia suryani; Ario Pradiska (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2026)
Abstract This study aims to analyze the effectiveness of the Traditional Bidar Boat Festival in the development of tourism along the Musi River by the Palembang City Tourism Office. This festival is a strategic initiative for cultural preservation and tourism promotion in Palembang City. This research uses a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. The study applies Sutrisno’s (2007) effectiveness indicators: program understanding, right on target, timeliness, achievement of objectives, and tangible change. The results indicate that the festival is effective in strengthening local cultural identity, increasing tourist visits, and boosting the local economy, particularly for MSMEs. However, challenges such as engaging the younger generation and optimizing digital promotion strategies remain. This study recommends cross-sectoral collaboration and innovation in programming to enhance the attractiveness and sustainability of the festival as a cultural tourism icon.